UNCONDITIONAL CONSERVATISM AS A MEDIATION BETWEEN LEVERAGE AND SIZE TO FIRM VALUE - DINUL ALFIAN AKBAR; AMRI AMIR; SRI RAHAYU; ASEP MACHPUDIN (Journal of Business Studies and Management Review, 2019)
This research is motivated by the controversy regarding the benefits of conservative accounting numbers, intended to determine the direct effect of leverage and size on firm value, and the indirect influence of these variables through unconditional conservatism as an intervening variable on firm values ​​in 2010 - 2017 on the Stock Exchange Indonesia. The results were that the variable unconditional conservatism can mediate the influence between size on firm value. There is a direct influence between leverage and size on firm value.